Botulinum toxin injection to the lateral rectus for the treatment of intractable diplopia - Broniarczyk-Loba, Anna; Laudańska-Olszewska, Iwona; Nowakowska, Olimpia (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The aim of the study is to evaluate the use of botuline A (BTXA) as a form of treatment for squinting patients with onerous diplopia. Two patients with exotropia and one patient with esotropia had injections of BTX A to the lateral rectus muscles of the affected side. The number of injections ranged from 1 to 2. Two patients went on to have surgery. All patients in our study found that BTX A improved their symptoms of diplopia. We conclude that BTX A has an important role in the treatment of squinting patients with burdensome diplopia.